The Implementation of Hot Seat Game to Teach English Vocabulary to Seventh Graders of Junior High School - Huda, Radewa Fibima (RETAIN, 2021)
The objective in this study was to discover the learners capacity in dominating vocabularies subsequent to instructing by utilizing hot seat technique and to depict the execution of hot seat ready to build the learners capacity toward English vocabulariesThe subject of the research is learner' at seventh graders of SMP NEGERI 1 KOTA MOJOKERTO in scholarly year 2018/2019. This member of the class comprise of 33 participants. This examination was directed by utilizing Classroom Action Research. The method of examining the information applied in this exploration was subjective and quantitative. The subjective information were taken from perception sheet. Meeting, and documentation. The quantitative information were taken from the pre-test and post- test. The data were taken from the result of the tests, which were completed in a cycle. In the cycle, four gatherings were directed. The understudies were given a test in types of pre-test and post-testThe result of the information show that the normal marks of the test is underneath the KKM (Passing Grade) with a level of not effective (81.8%) and effective with a rate (18.2%) In conclusion, the researcher found that the implementation of the hot seat game to teach understudies was not effective because the understudies was very large and also the time given by the tutor or teacher was quite restricted.